Validity and reliability of the 10-Item Adverse Childhood Experiences Questionnaire (ACE-10) among adolescents in the child welfare system - Oláh, Barnabás; Fekete, Zita; Kuritárné Szabó, Ildikó; Kovács-Tóth, Beáta (Frontiers in Public Health, 2023)
Introduction Multiple evidence suggests that the vast majority of children in the Child Welfare System (CWS) are victims of early, chronic, and multiple adverse childhood experiences. However, the 10-item version of the Adverse Childhood Experiences Questionnaire (ACE-10) has never been tested in such a particularly vulnerable population as adolescents living in the CWS. We aimed to assess the psychometric properties of the ACE-10 in a community sample of 240 Hungarian adolescents placed in family style group care (FGC) setting. Methods Demographic data, the 10-item version of the Adverse Childhood Experiences Questionnaire (ACE-10), the Strengths and Difficulties Questionnaire (SDQ), and the HBSC Bullying Measure were used. Results Our results showed acceptable internal consistency (α = 0.701) and item-total correlations (rpb = 0.25–0.65, p < 0.001). However, our results also reflect that item 6 (“Parental separation/divorce”) is weakly correlated with both the cumulative ACE score and the rest of the questionnaire items. When item 6 is removed, the 9-item version of the ACE produces more favorable consistency results (α = 0.729). Strong and significant associations of the cumulative ACE score with emotional and behavioral symptoms and bully victimization confirm the concurrent criterion validity of both versions of the instrument. Discussion Our findings suggest that ACE-9 and ACE-10 are viable screening tools for adverse childhood experiences in the CWS contributing to the advancement of trauma-informed care. We recommend considering the use of either the 9-item or the 10- item version in the light of the characteristics of the surveyed population. The implications and limitations are discussed.